Significance of reagent addition sequence in the amidation of carboxylic acids mediated by PPh3 and I2 - Sirilak Wangngae (2018)
© 2015 The Royal Society of Chemistry. The outcome of the amidation reaction mediated by PPh3-I2 was found to be highly dependent on the addition sequence of the reagents. When triethylamine was subjected to a mixture containing PPh3, I2, and a carboxylic acid, acid anhydride was generated almost instantly, before treatment with an amine, presumably via an attack of carboxylate ion onto the acyl function of an acyloxyphosphonium salt. Nevertheless, when a PPh3-I2 mixture was treated with an amine, then a carboxylic acid, prior to adding the base, amide was rapidly formed in high yield with high chemoselectivity, most likely through an intermediate O,N-pentacoordinate phosphorane species as confirmed by ESI-MS technique.